The Cloud Messenger : [compact disc] chamber version - Holst, Gustav, 1874-1934 (Delphian, 2020)
Telling the powerful fifth-century story of an exiled yaksha who spies a passing cloud and sends upon it a message of love to his distant wife in the Himalayas, Gustav Holst's choral-orchestral masterpiece is rich in its harmonic language and ingenious in its motivic construction, and points the way to Holst's next major work, The Planets.